Raytheon Advanced Miniature Cryocooler Characterization Testing. Issue 1 (November 2015) - Conrad, T; Yates, R; Schaefer, B; Bellis, L; Pillar, M; Barr, M
Abstract: The Raytheon Advanced Miniature (RAM) cryocooler is a flight packaged, high frequency pulse tube cooler with an integrated surge volume and inertance tube. Its design has been fully optimized to make use of the Raytheon Advanced Regenerator, resulting in improved efficiency relative to previous Raytheon pulse tube coolers. In this paper, thermodynamic characterization data for the RAM cryocooler is presented along with details of its design specifications.